2012
DOI: 10.1177/1474515111430879
|View full text |Cite
|
Sign up to set email alerts
|

Pain management after cardiac surgery: experience with a nurse-driven pain protocol

Abstract: This study shows that in post-cardiac surgery patients a significant reduction in VAS scores can be safely realized by a nurse-driven protocol. Furthermore, a reduction in time to achieve an acceptable pain score (VAS < 4) was realized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 29 publications
0
20
0
1
Order By: Relevance
“…One possible explanation is that not receiving additional pain medication (only 10% of patients still receive pain medication) accounts for the poorer quality of sleep. However, earlier studies in our centre show a decreased need for pain medication at this time [18].…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…One possible explanation is that not receiving additional pain medication (only 10% of patients still receive pain medication) accounts for the poorer quality of sleep. However, earlier studies in our centre show a decreased need for pain medication at this time [18].…”
Section: Discussionmentioning
confidence: 46%
“…The department has a nurse driven protocol which has been shown to result in lower pain scores (according to VAS) [18]. The efficacy of pain medication and low VAS scores on the quality of sleep need further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects were assessed by visual analogue scale (VAS) and medicated through the use of a pain protocol guided by nurses; others received medica ons conforming to the usual pain protocol. The results showed that pa ents medicated according to the rou ne of the ins tu on presented higher pain scale scores when compared to those treated with the nurse-guided protocol, who had a signifi cant reducon in pain, with greater comfort and safety (14) .…”
Section: Rev Esc Enfermmentioning
confidence: 82%
“…In another study conducted with a similar popula on, pa ents were evaluated for pain intensity and managed according to the protocol associated with a visual analogue scale (7) . The results showed be er management of pain intensity when protocols used were guided by nurses (8) .…”
Section: Introductionmentioning
confidence: 96%